PENGARUH FUNGI MIKORIZA ARBUSKULAR DAN KOMPOS PADA TANAMAN KEDELAI TERHADAP SIFAT KIMIA TANAH - Khairuna Khairuna; Syafruddin Syafruddin; Marlina Marlina (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
The aim of this research was to investigate effects of Arbuscular Mycorrhizal Fungi and compost on soil chemical properties under soybean. The research was conducted in Ude Village, Matangkuli Sub-District, Aceh Utara District, from June to November 2013. The experimental design was a factorial randomized complete block design with three replications. The first factor was Arbuscular Mycorrhizal Fungi doses, consisted of 4 levels: 0, 20, 40, and 60 g Pot-1. The second factor was compost doses, consisted of 4 levels: 0, 75, 150, and 225 g Pot-1. Variables measured were pH value, available P, and organic C soil. The results showed that compost doses gave significantly effect on pH value, available P and C-organic soil. Arbuscular Mycorrhizal Fungi doses increased the pH value, available P and organic C compared to without the fungi. There was a significant interaction between Arbuscular Mycorrhizal Fungi doses and compost doses on pH value and available P. Arbuscular Mycorrhizal Fungi dose of 60 g pot -1 and compost dose of 150 g pot-1 was able to increase the pH value. However, the best available P was found at Arbuscular Mycorrhizal Fungi dose of 60 g pot-1 and compost dose of 75 g pot-1.